Crystal structure of beta-MNX (M = Zr, Hf, X = Cl, Br) - Fogg, A; Evans, J; O'Hare, D (1998)
Superconductivity with critical temperatures of up to 25.5 K has recently been reported for alkali metal intercalates of β-MNX (M = Zr, Hf; X = Cl, Br); we have investigated the structures of these host lattices and found that they are not as reported in the literature but are isostructural with rhombohedral SmSI.